If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 3x + -23 Reorder the terms: 2x = -23 + 3x Solving 2x = -23 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2x + -3x = -23 + 3x + -3x Combine like terms: 2x + -3x = -1x -1x = -23 + 3x + -3x Combine like terms: 3x + -3x = 0 -1x = -23 + 0 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23
| y=-16x^2+12x+0.2 | | x+29=51 | | y-5=-9(x-4) | | X^3y^2+3X^2y-28X=0 | | -0.72E-4= | | 12x^2+3x+8x+2= | | 3x+1+x+4=9-x | | 12+8x=5x+3 | | 8m^2-11m-10=0 | | 76=7+2x | | 69=23x | | 2(z-3)=4(3+x) | | -90+3=a | | -90+3= | | -(x-4)=3 | | (5+y)(3y+7)=0 | | 6-3c=6-3c | | 8(x+4)=6x+80 | | 3k-10=11 | | 2*x+15= | | 5*243= | | 2x-2x-3=6 | | 4x+2.4=7.2 | | 5/243= | | 2x(x+3)=79 | | t*3-5=13 | | 7(6ab-4cd)= | | 4x-3=8y-1 | | -6x-15=4x+23 | | 2x-5y-1=0 | | 3x^4-4x^2+12x^2-16= | | -6x-15=-4x+23 |